Apostasy: between the Death Penalty and the Freedom (Criticizing the Thought of Jamal al-Banna) - Riyadi, Ahmad (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2018)
The death penalty for apostasy remains a contentious issue. Contemporary scholars view it as a violation of individual rights, particularly the freedom to choose or change one’s religion. They argue that the punishment stems from historical interpretations of Islamic law, often influenced by political considerations, rather than authentic religious sources. One such critic, Egyptian scholar Jamal Al-Banna, rejects the death penalty for apostates, contending that it has no basis in the Qur'an, hadith, or the practices of the Companions of the Prophet. This paper critically analyzes Al-Banna’s arguments against the death penalty and evaluates the hadiths he uses to support his position. The analysis concludes that the Qur'an and authentic (sahih) hadiths are not in contradiction. Rather, the misinterpretations of the hadiths in Al-Banna’s reasoning reflect a failure to reconcile them with the broader Islamic message. Thus, his critique does not hold up against a proper understanding of the texts.